Superwizja w zawodzie logopedy - Jastrzębowska-Jasińska, Aleksandra (Teoria i praktyka logopedyczna. Wybrane zagadnienia, 2018)
Supervision is a method of work to help a therapist to deal with the challenges that arise in his work and increase the quality of his services by working with himself. This method has so far been reserved in Poland for psychologists. However, taking into consideration problems and burdens at the therapist’s work, it is nowadays noticeable that the speech therapists also need to apply this method. The article will present the results of own research carried out on a group of 95 speech therapists focusing on the problems, also those psychological, arising in the work with a patient or cooperation with carer. The analysis presented in the article contains the answer to the question whether supervision, which is a kind of support for a practicing therapist, is needed and should also be introduced for speech therapists.